2015
DOI: 10.1186/s12920-014-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a gene expression signature of frequent COPD exacerbations in peripheral blood using network methods

Abstract: BackgroundExacerbations of chronic obstructive pulmonary disease (COPD), characterized by acute deterioration in symptoms, may be due to bacterial or viral infections, environmental exposures, or unknown factors. Exacerbation frequency may be a stable trait in COPD patients, which could imply genetic susceptibility. Observing the genes, networks, and pathways that are up- and down-regulated in COPD patients with differing susceptibility to exacerbations will help to elucidate the molecular signature and pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 32 publications
(28 reference statements)
3
87
0
Order By: Relevance
“…Gene-based coexpression network analyses together with expression single nucleotide polymorphism (eSNP) provide a powerful framework by pinpointing GWAS loci for eSNPs and mapping these GWAS hit genes to relevant modules/interactome representing disease-driven functional pathways (13,70). Bunyavanich et al (70) report mitochondria module from CD41+ lymphocytes gene expression data, showing an effect of the GWAS hits.…”
Section: Systems Biology Approach: Dissecting Complexity Of Asthma Comentioning
confidence: 99%
See 3 more Smart Citations
“…Gene-based coexpression network analyses together with expression single nucleotide polymorphism (eSNP) provide a powerful framework by pinpointing GWAS loci for eSNPs and mapping these GWAS hit genes to relevant modules/interactome representing disease-driven functional pathways (13,70). Bunyavanich et al (70) report mitochondria module from CD41+ lymphocytes gene expression data, showing an effect of the GWAS hits.…”
Section: Systems Biology Approach: Dissecting Complexity Of Asthma Comentioning
confidence: 99%
“…In the absence of such genotype data, coexpression network analyses alone can further provide meaningful interactomes of genes associated to asthma symptoms. Morrow et al (13) report putative hub genes from top five modules mostly associated with COPD exacerbation, including IGHM, KLRD1, AFF3, GPR56, GBP1, and GBP5. These genes are proposed as potential key regulators of the underlying functional pathways of B-cell receptor signaling pathway, protein ubiquitination, and cell adhesion molecules (13).…”
Section: Systems Biology Approach: Dissecting Complexity Of Asthma Comentioning
confidence: 99%
See 2 more Smart Citations
“…To characterise this heterogeneity at the molecular level, several studies have already used a number of different systems approaches. 1) WGCNA and GSEA showed that a molecular signature composed of gene modules related to B-cell activity, NK-cell activity or viral infection cellular markers might be detectable in peripheral blood months following COPD exacerbations [90]. 2) XUE et al [91] used other network-centric procedures to reveal an unexpected loss of inflammatory signature in COPD patients, as well as an activation-independent core signature for human and murine macrophages.…”
Section: Current Applications Of Systems Approaches In Respiratory Mementioning
confidence: 99%